Wellbeing: a Complete Reference Guide, Work and Wellbeing. - Chen, Peter Y.; Cooper, Cary L. (Wiley-Blackwell [Imprint] John Wiley & Sons, Incorporated, 2014)
Part of the six-volume reference set Wellbeing: A Complete Reference Guide, this volume is a comprehensive look at wellbeing in the workplace at organizational, managerial, and individual levels. Discusses the implications of theory and practice in the field of workplace wellbeingIncorporates not only coverage of workplace stress in relation to wellbeing, but also aspects of positive psychologyExplores the role of governments in promoting work place well beingPart of the six-volume set Wellbeing: A Complete Reference Guide, which brings together leading research on wellbeing from across the social sciencesTopics include work-life balance; coping strategies and characters of individuals; characteristics of workplaces and organizational strategies that are conducive to wellbeing; and many more.